DAMPAK PERKAWINAN DINI TERHADAP KESEJAHTERAAN KELUARGA (Studi di Desa Sendang Agung Kecamatan Plaosan Kabupaten Magetan) - Andika Budi Wicaksono; Ahmad Faruq (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Marriage (marriage) is a very sacred thing, both according to religious teachings and its position in Marriage Law no. 1 of 1974 in article 1 states that "marriage is a spiritual and physical bond between a man and a woman as husband and wife with the aim of forming a happy or eternal family (household) based on belief in the Almighty God. In this research there are three problem formulations, namely: 1 .) What are the factors that cause early marriage in Sendang Agung Village, Plaosan District, Magetan Regency? 2.) What are the impacts of underage marriage on household welfare?In this research the author uses empirical juridical research, the approach used in this research uses a qualitative approach, then the method of obtaining data in the field is through interviews and documentation. Meanwhile, the data processing process uses editing, classification, analysis and conclusion techniques.The results of this research show that the factors that cause early marriage in Sendang Agung Village, Plaosan District, Magetan Regency are due to self-will and also pregnancy outside of marriage. The impact of underage marriage turns out to be very influential on family welfare. This can be seen from several phenomena that occurred in Sendang Agung Village, Plaosan District, that after they married underage, the impact they felt was a lack of independence, burden on their parents, and also cases of divorce.